2010
DOI: 10.4097/kjae.2010.58.3.249
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Bonfils intubation fiberscopy and fiberoptic bronchoscopy in difficult airways assisted with direct laryngoscopy

Abstract: BackgroundTo evaluate the usefulness of Bonfils intubation fiberscope assisted by direct laryngoscopy (BIF-DL) and flexible fiberoptic bronchoscope assisted by direct laryngoscopy (FOB-DL) using video recording in cases of unanticipated difficult intubation with respect to the time required to visualize the vocal cords and place the endotracheal tube. We compared two fiberscopes in patients with authentic difficult airways.MethodsIn this randomized, controlled clinical trial, 40 patients (grade 3 according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…Rudolph et al 11 had a 100% success rate with BRF in the unanticipated difficult airway (n = 116), including success with BRF after 2 failed attempts at fiberoptic bronchoscopy intubation. Kim et al 10 had a 90% (18/20) success rate with BRF. In this study, Cormack and Lehane grade III at DL was observed in 6 (1.5%) patients, an incidence similar to previous studies that noted only the best glottic view obtained with or without backward upward rightward pressure 28 ; BRF intubation without assistance with a laryngoscope was successful in 5 of these 6 patients (83%).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Rudolph et al 11 had a 100% success rate with BRF in the unanticipated difficult airway (n = 116), including success with BRF after 2 failed attempts at fiberoptic bronchoscopy intubation. Kim et al 10 had a 90% (18/20) success rate with BRF. In this study, Cormack and Lehane grade III at DL was observed in 6 (1.5%) patients, an incidence similar to previous studies that noted only the best glottic view obtained with or without backward upward rightward pressure 28 ; BRF intubation without assistance with a laryngoscope was successful in 5 of these 6 patients (83%).…”
Section: Discussionmentioning
confidence: 97%
“…In all 4 cases where intubation with the BRF alone was not successful, failure to visualize the glottis appeared to be the result of difficulty in mobilizing the epiglottis to create an opening between it and the posterior pharyngeal wall without the BRF passing directly into the esophagus. DL performed simultaneously with BRF is a technique that has been described before 10 and that allows the anesthesiologist to lift the epiglottis off the posterior pharynx. When attempted in 2 of the cases of failed BRF in this study, this technique proved successful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are fast to set up, portable and more durable than flexible scopes . Their use may be associated with a higher success rate than Macintosh laryngoscopes in difficult airway scenarios , and, compared with flexible scopes, rigid scopes may reduce intubation time . Also, complication rates are similar to flexible scopes and the Macintosh laryngoscope .…”
Section: Introductionmentioning
confidence: 99%
“…Macroglossia was identified as an independent risk factor in other studies as well 27 . Many studies indicate the necessity of additional equipment besides the standard Macintosh laryngoscope, primarily fiber optic bronchoscope in order to resolve a problematic airway [28][29][30] . In all patients, including those who had a very high-risk score and where it was almost certain that DI would occur, we primarily tried to intubate in a conventional manner, using Macintosh laryngoscope.…”
Section: Nevena Kalezić Et Almentioning
confidence: 99%